Livestock’s critical role in net-zero food systems - Wollenberg, Eva Karoline; Costa, Ciniro (Bioversity International and the International Center for Tropical Agriculture, 2022)
Presentation on the critical role of livestock in the global agenda for food systems to achieve net zero emissions presented by Lina Wollenberg and Ciniro Costa at COP27, Nov 2022, Sharm el-Sheikh, Egypt.